On the Chinese’s Exchange Rate Regime: A Different Approach - Mele, Marco (International Journal of Economics and Financial Issues, 2019)
This paper will prove, through a financial and econometric model, a different estimation approach on the Chinese’ basket peg. In particular, this study proposes a new system for calculating the numeraire in exchange rates of the major currencies present in Chinese basket-peg. We will analyze the values of exchange rates in the financial markets, particularly in the Forex market and Binary options. Then, after choosing the three currencies that have characteristics of low volatility, we will find our numeraire that will be determined by average every 30 minutes. Finally, we will do an econometric estimation. Keywords: Exchange Rate Regime, Chinese Basket peg, Forex Market, Binary options. JEL Classifications: F22, F42, F44 DOI: https://doi.org/10.32479/ijefi.6539